2007
DOI: 10.1111/j.1365-2958.2007.05795.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a key residue in the type II secretion system ATPase uncouples ATP hydrolysis from protein translocation

Abstract: SummaryMembrane-associated ATPase constitutes an essential element common to all secretion machineries in Gram-negative bacteria. How ATP hydrolysis by these ATPases is coupled to secretion process remains unclear. Here we identified R286 as a key residue in the type II secretion system (T2SS) ATPase XpsE of Xanthomonas campestris that plays a pivotal role in coupling ATP hydrolysis to protein translocation. Mutation of R286 to alanine made XpsE hydrolyse ATP at a rate five times that of the wild-type XpsE. Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This variant of GspE EpsE lacked the N1D and crystallized in a helical arrangement with 6 1 symmetry (Robien et al, 2003). Solution studies indicate hexamer formation of the GspE XpsE from the Xanthomonas campestris T2SS upon the addition of nucleotides (Shiue et al, 2007). Activity measurements of V. cholerae GspE EpsE showed that oligomers of an approximately hexameric size according to gel filtration analysis possess much higher activity than monomers, but hexamers are only present in small amounts (Camberg and Sandkvist, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This variant of GspE EpsE lacked the N1D and crystallized in a helical arrangement with 6 1 symmetry (Robien et al, 2003). Solution studies indicate hexamer formation of the GspE XpsE from the Xanthomonas campestris T2SS upon the addition of nucleotides (Shiue et al, 2007). Activity measurements of V. cholerae GspE EpsE showed that oligomers of an approximately hexameric size according to gel filtration analysis possess much higher activity than monomers, but hexamers are only present in small amounts (Camberg and Sandkvist, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Type II‐dependent protein transport is probably energized by a cytoplasmic ATPase associated with the secretion apparatus at the inner membrane (Chen et al. , 2005; Shiue et al. , 2006, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous assembly and disassembly of the pseudopilus presumably pushes T2S substrates through the outer membrane secretin (Sandkvist, 2001;Cianciotto, 2005). Type II-dependent protein transport is probably energized by a cytoplasmic ATPase associated with the secretion apparatus at the inner membrane (Chen et al, 2005;Shiue et al, 2006Shiue et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The EpsE-Arg 225 equivalent in Xanthomonas campestris XpsE (XpsE-Arg 286 ) has been pinpointed as being an important residue for sensing the bound nucleotide and coordinating the movement of the NTD relative to the CTD (33). The EpsEArg 225 and Arg 210 counterparts in both AfGspE and PaPilT have been shown to come close to the bound nucleotide suggesting a conserved function (20,33). Interestingly, the equivalent arginines in PaPilT structure show marked conformational differences in the three observed states (19).…”
Section: Discussionmentioning
confidence: 99%
“…1D, the Arg 225 subunit C from EpsE moves sufficiently close to the ␥-phosphate of the bound nucleotide to directly participate in ATP coordination or hydrolysis. The EpsE-Arg 225 equivalent in Xanthomonas campestris XpsE (XpsE-Arg 286 ) has been pinpointed as being an important residue for sensing the bound nucleotide and coordinating the movement of the NTD relative to the CTD (33). The EpsEArg 225 and Arg 210 counterparts in both AfGspE and PaPilT have been shown to come close to the bound nucleotide suggesting a conserved function (20,33).…”
Section: Discussionmentioning
confidence: 99%